Life satisfaction and self-employment: A matching approach - Martin Binder; Alex Coad (Max Planck Institute of Economics, 2010)
Despite lower incomes, the self-employed consistently report higher satisfaction with their jobs. But are self-employed individuals also happier, more satisfied with their lives as a whole? High job satisfaction might cause them to neglect other important domains of life, such that the fulfilling job crowds out other pleasures, leaving the individual on the whole not happier than others. Moreover, self-employment is often chosen to escape unemployment, not for the associated autonomy that seems to account for the high job satisfaction. We apply matching estimators that allow us to better take into account the above-mentioned considerations and construct an appropriate control group. Using the BHPS data set that comprises a large nationally representative sample of the British populace, we find that individuals who move from regular employment into self-employment experience an increase in life satisfaction (up to two years later), while individuals moving from unemployment to self-employment are not more satisfied than their counterparts moving from unemployment to regular employment. We argue that these groups correspond to opportunity and necessity entrepreneurship, respectively. These findings are robust with regard to different measures of subjective well-being as well as choice of matching variables, and also robustness exercises involving simulated confounders.
urn:nbn:de:gbv:27-20110628-152532-3
Keywords: J24; J28; C21; 330; self-employment; happiness; matching estimators; unemployment; BHPS; necessity entrepreneurship; Zufriedenheit; Selbstständige; Arbeitslosigkeit; Matching; Schätzung; Großbritannien